2017
DOI: 10.1002/pd.5093
|View full text |Cite
|
Sign up to set email alerts
|

Parental response to severe or lethal prenatal diagnosis: a systematic review of qualitative studies

Abstract: Clinicians can support parental coping following a severe prenatal diagnosis through continued dialogue and collaboration. Further research is needed on the experiences of parents who choose to terminate a pregnancy following prenatal diagnosis. © 2017 John Wiley & Sons, Ltd.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
52
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 34 publications
(59 citation statements)
references
References 62 publications
(191 reference statements)
7
52
0
Order By: Relevance
“…Our findings regarding parents' needs concur with results from an integrative review into mothers' experiences of prenatal diagnoses which found that HCPs' communication skills helped them cope 13 . Our results also converge with a review of qualitative studies into experiences of lethal prenatal diagnoses, which suggested that parents valued timely, written information about the diagnosis 14 . In line with a literature review into breaking bad news in prenatal settings, our results suggested that expectant parents wanted HCPs to communicate their findings in clear but sensitive terms 15 .…”
Section: Discussionsupporting
confidence: 83%
“…Our findings regarding parents' needs concur with results from an integrative review into mothers' experiences of prenatal diagnoses which found that HCPs' communication skills helped them cope 13 . Our results also converge with a review of qualitative studies into experiences of lethal prenatal diagnoses, which suggested that parents valued timely, written information about the diagnosis 14 . In line with a literature review into breaking bad news in prenatal settings, our results suggested that expectant parents wanted HCPs to communicate their findings in clear but sensitive terms 15 .…”
Section: Discussionsupporting
confidence: 83%
“…We have mainly experienced how WES provided couples with informed reproductive choices enabling compassionate care of the newborn. Parents express a better coping with the situation when knowing the diagnosis of the child 15,18 . We have also experienced that a normal result of WES caused some relief in the light of a decreased risk of many severe diagnoses.…”
Section: Discussionmentioning
confidence: 99%
“…The geneticist/counselor must have confidence in a pathogenic genetic result even without a supportive fetal phenotype, but must also be cautious of wrong interpretations and insist on reverse phenotyping when necessary. The health professionals need to develop skills in how to communicate with pregnant women in a new territory of uncertainty, urgency, and few options 18,26,27 . Additional collaborations need to be formed between neonatologists, midwives, and the prenatal and genetic teams.…”
Section: Discussionmentioning
confidence: 99%
“…A recent systematic review found that parents who choose to continue the pregnancy following a severe diagnosis – such as DS – requested timely and adequate information, and continued and empathic interactions with clinicians . In Denmark, the number of women and couples who choose to continue the pregnancy is very low, and it is very important that the needs of this subpopulation are not overlooked and that the decision to continue is positively supported and legitimized by clinicians.…”
Section: Discussionmentioning
confidence: 99%